The Use of New Media in a Virtual Website Exhibition A Mild "A Space" - Renzina, Yudha Delonix (Indonesian Journal of Visual Culture, Design, and Cinema, 2023)
The Covid-19 pandemic that hit various countries has limited the public's space movement in the community. The emergence of new rules in the new normal era makes difficult for artists to perform any art performances. A MILD as one of the biggest drivers of the economy in Indonesia held a virtual exhibition called "A space" through the power of the internet network. The appearance of this new media will facilitate the artists to be able to work again and help the public to continue enjoy the art in the pandemic era. The research method that used is descriptive exploratory analysis to examine the phenomena that are happening descriptively. The purpose of this research is to provide a discourse or view to the public as a new perspective in viewing an exhibition or work of art.